Diversidad: retos para una educación inclusiva - Bonilla Mata, Víctor H. (2002)
This article deals with the inclusion and participation as requisites for development. Education has a pending debt with humanity: the human diversity as a social project, and the urgency to acknowledge its content and historical meaning and the challenge the difference issue poses to education in the XXI century.